PENERAPAN ANALISIS FAKTOR REDUCTION DALAM DETERMINASI IMPLEMENTASI STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM) - Anna Apriana Hidayanti; Agus Khazin Fauzi; Baiq Desthania Prathama (Jurnal Ilmiah Wahana Akuntansi, 2020)
The current research was carried out to investigate the correlation of educational background, perceived usefulness, perceived ease of use, socialization and quality of human resources with (SAK-EMKM) Implementation by reducing variables to several factors using the factor analysis method. Data collection in this study with a questionnaire given to the owner of the by Micro, Small and Medium Enterprises (MSMB) in Mataram city and 40 UMKM samples were obtained using purposive sampling technique, factor analysis aim to reduce the dimensionality of a set of data and clearly designed with the objective to identify certain unobservable factors from the observed variables. The results of this study were formed into two factors: 1st factor is these factors are termed the perception of the owner of the by Micro, Small and Medium Enterprises (MSMB) formed from the perception and variables using SAK EMKM perception then against SAK-EMKM implementation has a positive effect. 2nd factor is these factor was human resources factors formed from the educational background variable and the quality of human resources variable and against SAK-EMKM implementation has positive correlation.